A method for preparing sodium iron sulfate as a sodium positive electrode material
By using iron, sodium, sulfuric acid/sulfate and other raw materials for precipitation and crystallization reaction at lower temperatures, a high crystallinity sodium iron sulfate positive electrode material is prepared, which solves the long process flow, high energy consumption and The problem of low material performance has achieved process simplification, reduced energy consumption and improved material performance.
Patent Information
- Application Number
- CN202411052040.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The existing sodium electropositive electrode materials have a long process, high energy consumption, high production costs, and low compaction density and capacity of the prepared materials.
The precipitation and crystallization reaction is carried out at a lower temperature (90~100℃) to prepare a high crystallinity positive electrode material with high crystallinity.
The process flow is simplified, energy consumption is reduced, and production costs is reduced. At the same time, the compaction density and 0.1C discharge capacity of the cathode material of sodium ferrosulfate are improved.
Smart Images

Figure CN118619355B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode materials, and in particular to a method for preparing sodium iron sulfate, a sodium-based positive electrode material. Background Art
[0002] In recent years, with the rapid development of the global electric vehicle industry, the production capacity of electric vehicle power batteries has become a bottleneck restricting the development of electric vehicles. The battery positive electrode material mainly uses ternary lithium batteries, but due to the continued high price of lithium carbonate, vigorously developing sodium ion batteries has become a popular direction now. On the one hand, sodium resources are very abundant and will not become a resource that restricts development; on the other hand, sodium resources are cheap. The price of sodium carbonate is 3,000 to 5,000 yuan / ton, while the price of lithium carbonate is 90,000 to 150,000 yuan / ton. Compared with lithium carbonate, sodium carbonate has a great price advantage. In addition, although the radius of sodium ions is larger than that of lithium ions, their Stokes radius is smaller than that of lithium ions, and their transmission speed in the electrolyte is faster than that of lithium ions, so their low temperature and rate performance are better than lithium-ion batteries.
[0003] There are many types of positive electrode materials for sodium-ion batteries, and more than 100 types are being researched and developed. However, the mainstream sodium-ion positive electrode materials include nickel-cobalt-manganese ternary sodium positive electrode materials, sodium iron sulfate positive electrode materials, polyanion sodium positive electrode materials, and Prussian series sodium positive electrode materials. Sodium-ion positive electrode materials and sodium-ion batteries are in the stage of industrialization and rapid development, and the positive electrode material route has not yet been fully finalized. From the perspective of future market development, with the development of technology and the formation of the industrial chain, sodium-ion batteries will play a pivotal role in the two markets of power and energy storage in the future.
[0004] The preparation of existing sodium positive electrode materials has the disadvantages of long process flow, high energy consumption, high production cost, and low compaction density and capacity of the prepared materials. For example, patent CN115863570A uses a two-step method to prepare sodium iron sulfate positive electrode materials. It first uses sodium sulfate, iron sulfate, vanadium sulfate, and urea as raw materials to prepare yellow sodium iron vanadium by high temperature and high pressure hydrothermal reaction at 130~150℃ for 1~2h. In the second step, the prepared yellow sodium iron vanadium, sodium sulfate, phosphoric acid and ammonium bicarbonate are used as raw materials for ball milling and spray drying, and then calcined at 400~550℃ for 6~9h to obtain sodium iron sulfate positive material. The preparation process is long and the process is complicated. The first step of preparing yellow sodium iron vanadium is a hydrothermal method, which requires a pressure vessel and a high crystallization temperature (130~150℃). The second step requires high energy consumption and time-consuming processes such as ball milling, spray drying, and high temperature calcination. The process flow is long, the energy consumption is high, and it is not conducive to industrialization. In addition, the compaction density of the prepared sodium iron sulfate positive electrode material is relatively low (2.0~2.2g / cc), and the 0.1C discharge capacity is also relatively low (100~110mAh / g). Summary of the invention
[0005] In view of the problems in the prior art of the preparation of sodium positive electrode materials, such as long process flow, high energy consumption, high production cost, and low compaction density and capacity of the prepared materials, the present invention provides a method for preparing sodium positive electrode material sodium iron sulfate to solve the above problems. The present invention uses raw materials such as iron source, sodium source, sulfuric acid / sulfate, etc., and precipitates and crystallizes at a relatively low temperature to prepare a sodium iron sulfate positive electrode material with high crystallinity. The present invention has the advantages of short process flow, simple process, low energy consumption, and easy industrialization, and the prepared sodium iron sulfate positive electrode material has the advantages of high compaction density (2.42-2.47g / cc) and high 0.1C discharge capacity (128-130mAh / g).
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing sodium iron sulfate, a sodium positive electrode material, comprises the following steps:
[0008] (1) preparing an aqueous solution of an iron source and an aqueous solution of a sodium source respectively and setting them aside; then adding an acid to the aqueous solution of the iron source;
[0009] (2) adding the sodium source aqueous solution to the iron source aqueous solution to prepare a slurry;
[0010] (3) Add an oxidant, and then add alkali solution to adjust the pH value to 3-5;
[0011] (4) crystallization reaction at 90-100°C for 3-5h, and the product after the reaction is washed and dried to obtain sodium iron sulfate, a positive electrode material for sodium battery;
[0012] The iron source is at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate or ferrous chloride; the sodium source is at least one of sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium bicarbonate, sodium sulfate or sodium bisulfate; the acid is one of concentrated sulfuric acid, nitric acid, hydrochloric acid or hypochlorous acid; and at least one of the iron source, sodium source and acid contains sulfate or bisulfate.
[0013] Furthermore, in step (2), the molar ratio of the sum of sodium, iron, sulfate and hydrogen sulfate in the slurry is 1:3:2.0-2.5.
[0014] Furthermore, in step (2), the sodium source aqueous solution is added to the iron source aqueous solution for 50 to 90 minutes, preferably 70 minutes.
[0015] Furthermore, in step (2), the sodium source aqueous solution is added to the continuously stirred iron source aqueous solution at a stirring rate of 100-600 rpm.
[0016] Furthermore, in step (3), the oxidant is at least one of hydrogen peroxide, oxygen, air, ozone, peracetic acid or potassium permanganate.
[0017] Furthermore, in step (3), the alkali solution is at least one of sodium hydroxide, sodium carbonate, disodium hydrogen phosphate or trisodium phosphate.
[0018] Furthermore, in the step (4), the crystallization reaction is stirred at a speed of 100-600 rpm.
[0019] Furthermore, in step (4), the drying temperature is 100-150° C., and the drying time is 5-10 hours.
[0020] The beneficial effects of the present invention are:
[0021] The present invention adopts iron source, sodium source, sulfuric acid / sulfate etc. as raw materials, and prepares sodium ferric sulfate positive electrode material by precipitation crystallization reaction at relatively low temperature (90-100°C). The present invention has the advantages of short process flow, low energy consumption, easy industrialization, etc., and the prepared sodium ferric sulfate positive electrode material has the characteristics of high compaction density and high capacity, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 This is the XRD diagram of sodium iron sulfate, the sodium battery positive electrode material prepared in Example 3.
[0024] Figure 2 This is a SEM image of sodium iron sulfate, a sodium-based positive electrode material prepared in Example 3. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] Example 1
[0027] A method for preparing sodium iron sulfate, a sodium positive electrode material, comprises the following steps:
[0028] (1) Prepare 2 L of ferrous sulfate solution with a concentration of 1.5 mol / L and 2 L of sodium dihydrogen phosphate solution with a concentration of 0.5 mol / L, then add the ferrous sulfate solution into a reactor with a stirring rate of 200 rpm, then add 1 L of nitric acid solution with a concentration of 1.2 mol / L and stir evenly;
[0029] (2) adding disodium hydrogen phosphate solution into the reaction kettle for 70 minutes to obtain a slurry;
[0030] (3) Weigh 251.8 g of 27% hydrogen peroxide and add it to the reactor for 20 min; then add sodium carbonate to adjust the pH to 3;
[0031] (4) The reaction solution was heated to 97°C and kept warm for 4 h to obtain a slurry of sodium ferric sulfate; the slurry was filtered and the filter cake was washed until the conductivity of the filtrate was less than 2000 μS / cm; the filter cake was dried at 120°C for 7 h to obtain 1.47 kg of sodium ferric sulfate.
[0032] Example 2
[0033] A method for preparing sodium iron sulfate, a sodium positive electrode material, comprises the following steps:
[0034] (1) Prepare 4 L of 1.5 mol / L ferrous chloride solution and 2 L of 1.0 mol / L sodium phosphate solution, then add the ferrous chloride solution into a reactor with a stirring rate of 200 rpm, then add 1 L of 98% concentrated sulfuric acid and stir evenly;
[0035] (2) adding sodium phosphate solution into the reaction kettle for 60 minutes to obtain a slurry;
[0036] (3) Weigh 518.5 g of 27% hydrogen peroxide and add it to the reactor for 20 min; then add sodium hydroxide to adjust the pH to 4;
[0037] (4) The reaction solution was heated to 97°C and kept warm for 4 h to obtain a slurry of sodium ferric sulfate; the mixture was filtered and the filter cake was washed until the conductivity of the filtrate was less than 2000 μS / cm; the filter cake was dried at 120°C for 7 h to obtain 2.93 kg of sodium ferric sulfate.
[0038] Example 3
[0039] A method for preparing sodium iron sulfate, a sodium positive electrode material, comprises the following steps:
[0040] (1) Prepare 21 L of ferrous oxalate solution with a concentration of 1.0 mol / L, prepare 7 L of sodium dihydrogen phosphate solution with a concentration of 1.0 mol / L, then add the ferrous oxalate solution into a reactor, stir the reactor at a rate of 300 rpm, then add 10 L of sulfuric acid solution with a concentration of 1.2 mol / L, and stir evenly;
[0041] (2) adding sodium dihydrogen phosphate solution into the reaction kettle for 60 minutes to obtain a slurry;
[0042] (3) Weigh 2.58 kg of 27% hydrogen peroxide and add it to the reactor for 60 minutes; then add sodium carbonate to adjust the pH value to 3;
[0043] (4) The reaction solution was heated to 97°C and kept warm for 5 h to obtain a slurry of sodium ferric sulfate; the mixture was filtered and the filter cake was washed until the conductivity of the filtrate was less than 2000 μS / cm; the filter cake was dried at 120°C for 7 h to obtain 10.27 kg of sodium ferric sulfate.
[0044] The sodium iron sulfate prepared in Example 3 was subjected to X-ray diffraction detection, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the sodium iron sulfate obtained after drying is pure phase sodium iron sulfate. The sodium iron sulfate prepared in Example 3 was subjected to SEM detection, and the results are as follows: Figure 2 As shown, from Figure 2 It can be seen that sodium iron sulfate is a nanowire structure with a wire length of 200~300nm and a wire diameter of 10~20nm.
[0045] Comparative Example 1
[0046] Example 1 of CN115863570A was used to prepare the sodium positive electrode material.
[0047] (1) Preparation of sodium ferroaluminate particles
[0048] 1.92 kg of sodium sulfate, 12.00 kg of ferric sulfate, 52 g of titanyl sulfate, 4.11 kg of urea and 54 kg of pure water are mixed together, heated to 100°C while stirring, reacted at this temperature at a stirring speed of 200 r / min for 2 hours, then heated to 140°C for 1.5 hours, then washed with pure water using a filter press until the conductivity of the washing water is less than 150 μS / cm; flash dried to obtain doped high-crystallinity sodium iron alum particles.
[0049] Among the raw materials used, the purity of sodium sulfate is 99.7wt%, the content of calcium and magnesium is less than 100ppm, and the content of other impurities is less than 50ppm; the purity of iron sulfate is 99.2wt%, Fe 2+The content of is less than 100ppm, the content of calcium and magnesium is less than 120ppm, the content of other impurities is less than 60ppm, and its pH is 1.3; the water-insoluble matter of urea is less than 150ppm, and cation exchange resin is required to adsorb impurity cations before use.
[0050] (2) Add 4.85 kg of the obtained yellow sodium ferroalcite, 3.57 kg of sodium sulfate and 1.00 kg of phosphoric acid into a mixed solution of glucose and pyridine (0.27 kg of glucose, 0.012 kg of pyridine and 15.38 kg of water);
[0051] (3) After stirring and mixing, add the mixture into a ball mill and grind until the particle size of the slurry is 0.18 μm;
[0052] (4) spray drying, the particle size of the spray drying is 23 μm, and the moisture content is less than 0.5 wt%;
[0053] (5) The dried material is calcined. During the calcination process, the heating rate is 1.7°C / h. Then, the material is kept warm at 460°C for 8 hours. The material temperature is then cooled to ≤100°C at a rate of 1.3°C / h. During the calcination process, the humidity in the furnace is controlled at 2.5%. The calcination is carried out in a nitrogen atmosphere with an oxygen content of 2.7ppm. The sodium iron sulfate positive electrode material Na 12 Fe 6 (SO 4 ) 9 (PO 4 ) 2 ;
[0054] (6) The calcined material is subjected to air flow pulverization to a particle size of 1.56 μm, and then sieved using an ultrasonic vibrating screen and 100 mesh sieve; iron is then removed using an electromagnetic iron remover to remove iron to a magnetic foreign matter content of 0.37 ppm; and finally vacuum packaged.
[0055] Test Case
[0056] The sodium iron sulfate prepared in Examples 1 to 3 and the sodium iron sulfate prepared in Comparative Example 1 were tested for compaction density. Carbon coating was then performed under the same conditions, and the carbon-coated material was prepared into a button-type battery under the same conditions according to a conventional method, and then its electrical properties were tested under the same conditions according to a conventional method in the art. The electrical performance test results of Examples 1 to 3 and Comparative Example 1 are shown in Table 1 below.
[0057] Table 1 - Sodium ferric sulfate electrical performance test results
[0058]
[0059] As can be seen from Table 1, the sodium iron sulfate prepared by the example has good electrical properties, with a 0.1C discharge capacity of 128-130 mAh / g, and a high discharge voltage of 3.75 V. The prepared sodium iron sulfate product has high capacity and high voltage, thus having a high energy density, and the process operation is simple and has the ability of industrial production. The positive electrode material prepared in Comparative Example 1 has a low compaction (2.07 g / cc), and the capacity, discharge voltage, discharge efficiency, etc. are also low.
[0060] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for preparing sodium iron sulfate, a sodium positive electrode material, characterized in that: The following steps are involved: (1) preparing an aqueous solution of an iron source and an aqueous solution of a sodium source respectively and setting them aside; then adding an acid to the aqueous solution of the iron source; (2) adding the sodium source aqueous solution to the iron source aqueous solution to prepare a slurry; (3) Add an oxidant, and then add alkali solution to adjust the pH value to 3-5; (4) crystallization reaction at 90-100°C for 3-5h, and the product after the reaction is washed and dried to obtain sodium iron sulfate, a positive electrode material for sodium battery; The iron source is at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate or ferrous chloride; the sodium source is at least one of sodium monohydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; the acid is one of concentrated sulfuric acid, nitric acid, hydrochloric acid or hypochlorous acid; and at least one of the iron source, sodium source and acid contains sulfate or hydrogen sulfate; In the step (2), the molar ratio of the sum of sodium, iron, sulfate and hydrogen sulfate in the slurry is 1:3:2.0-2.
5.
2. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (2), the sodium source aqueous solution is added to the iron source aqueous solution for 50 to 90 minutes.
3. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (2), the sodium source aqueous solution is added to the iron source aqueous solution for 70 minutes.
4. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (2), the sodium source aqueous solution is added to the continuously stirred iron source aqueous solution at a stirring rate of 100 to 600 rpm.
5. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In step (3), the oxidant is at least one of hydrogen peroxide, oxygen, air, ozone, peracetic acid or potassium permanganate.
6. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (3), the alkali solution is at least one of sodium hydroxide, sodium carbonate, disodium hydrogen phosphate or trisodium phosphate.
7. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (4), stirring is performed during the crystallization reaction at a speed of 100 to 600 rpm.
8. The method for preparing sodium iron sulfate as a sodium positive electrode material according to claim 1, characterized in that: In the step (4), the drying temperature is 100-150° C. and the drying time is 5-10 hours.
Citation Information
Patent Citations
Iron series pigment ihleite and preparation method thereof
CN105836812A